2018
DOI: 10.1155/2018/1052960
|View full text |Cite
|
Sign up to set email alerts
|

Extragastrointestinal Stromal Tumor: A Differential Diagnosis of Compressive Upper Abdominal Tumor

Abstract: Introduction Extragastrointestinal stromal tumors (EGIST) are rare mesenchymal tumor lesions located outside the gastrointestinal tract. A rare compressing tumor with difficult diagnosis is reported. Presentation of the Case A male patient, 63 years old, was admitted in the emergency room complaining of stretching and continuous abdominal pain for one day. He took Hyoscine, with partial improvement of symptoms, but got worse due to hyporexia, and the abdominal pain persisted. The patient also reported early sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…The omental E-GIST may more closely resemble gastric stromal tumors whereas the mesenteric tumors may mirror small bowel stromal tumors [ 9 ]. Studies have revealed that E-GIST tumors show positive immunohistochemistry in 93.3% for CD117 (c-kit receptor), 70% for CD34, 44% for neuron-specific enolase, 26% for smooth muscle actin, 10% for S100 and 4% for desmin [ 2 , 9 ]. However, there are GISTs that have a mutation of platelet-derived growth factor receptor alpha (PDGFRA) instead of c-KIT and therefore they do not show the characteristic CD117 positive immunostaining [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The omental E-GIST may more closely resemble gastric stromal tumors whereas the mesenteric tumors may mirror small bowel stromal tumors [ 9 ]. Studies have revealed that E-GIST tumors show positive immunohistochemistry in 93.3% for CD117 (c-kit receptor), 70% for CD34, 44% for neuron-specific enolase, 26% for smooth muscle actin, 10% for S100 and 4% for desmin [ 2 , 9 ]. However, there are GISTs that have a mutation of platelet-derived growth factor receptor alpha (PDGFRA) instead of c-KIT and therefore they do not show the characteristic CD117 positive immunostaining [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…GIST needs to be distinguished from leiomyoma, schwannoma, inflammatory fibroid polyps and fibromatosis [ 2 , 7 ]. Peritoneal mesotheliomas with sarcomatoid differentiation may mimic E-GIST and needs to be differentiated [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastrointestinal stromal tumours (GISTs) are the most common non-epithelial gastric neoplasms and the most frequent mesenchymal tumour to affect the digestive tract [1][2][3][4]. These tumours are believed to arise from precursors of the interstitial cells of Cajal, regarded as the gastrointestinal "pacemaker" [5].…”
Section: Introductionmentioning
confidence: 99%
“…Gastrointestinal stromal tumours (GISTs) are mesenchymal neoplasms that can appear in any segment of the gastrointestinal (GI) tract and account for 0.1–3% of all GI tumours. They can be benign and malignant, and there are three histological types: spindle, epithelial, and mixed-cell [1]. Almost all GISTs express immunopositivity for CD117, a C-Kit proto-oncogene protein, which shows an increase in the function of C-Kit gene, which encodes growth factor receptor with tyrosine kinase activity [2].…”
mentioning
confidence: 99%